Building automation - important technical aspect of the energy efficiency - Мельнікова, Любов Василівна; Бушер, Віктор Володимирович; Онищенко, Олег Анатолійович; Шестака, Анатолій Іванович (Eastern-European Journal of Enterprise Technologies, 2012)
The urgency of the problem of buildings energy consumption is presented, key measures and actions taken at the governmental level of the leading countries of Europe and the world are reported in this article